Characterization of lactic acid bacteria with antimicrobial activity isolated from cream cheese from Chiapas, Mexico - Wong-Villarreal, Arnoldo (Universidad Autónoma de Tamaulipas, 2021)
Chiapas cream cheese is an artisanal product manufactured in different regions of Mexico. The ability of lactic bacteria to produce large amounts of lactic and acetic acid has the effect of decreasing the pH, considered one of the primary factors in the inhibition of undesirable microorganisms such as pathogens and coliform bacteria, in dairy foods. The objective of this work was to isolate lactic acid bacteria and evaluate their antagonistic effect against pathogenic bacteria in vitro, as well as their effect against pathogens that are present in milk when they are added in the preparation of cream cheese. Strains of lactic bacteria were isolated from cream cheese from Chiapas, Mexico. Isolates were identified by API 50CH biochemical tests and 16S ribosomal gene sequences. The bacteria under study were used in pathogen growth inhibition tests. The production of acetic and lactic acid was quantified by gas chromatography coupled to masses in the cheeses at the beginning and 10 d after its elaboration. 203 bacterial strains were isolated, 82 of which had the ability to inhibit the growth of 7 pathogenic bacterial strains. The strains were identified by the partial sequence of the 16S ribosomal gene as belonging to the genus Lactobacillus; The addition of these strains in the elaboration of cream cheese reduces or eliminates coliforms, Staphylococcus aureus, molds and yeasts, while in the cheese made with pasteurized milk 290 CFU/mL of molds and yeasts were detected. These results suggest that Lactobacillus strains isolated from Chiapas artisanal cream cheese has the potential to be used as a starter culture with bioconservation  activity  in  this  and  similar  products.